Role of integrated crop-livestock system on amelioration of heat stress on crossbred Brazilian sheep in semiarid region of northeastern Brazil - Lins, José Gabriel Gonçalves [UNESP]; Rodrigues, Serginara David [UNESP]; Albuquerque, Ana Cláudia Alexandre [UNESP]; Marques, Ana Valéria Mello de Souza (Elsevier, 2021)
The aim of this study was to evaluate the effect of livestock rearing system, sheepfold vs. integrated crop-livestock system, on heat tolerance and physiological traits of crossbred sheep (Santa Ines x Dorper) in the semiarid region of Brazilian Northeastern. Forty crossbred hair ewes (Santa Ines x Dorper), 15–48 months old, were assigned to two treatments: 20 in treatment I (SF – Sheepfold) and 20 in treatment II (ICL - integrated crop-livestock system with tall coconut palm trees). Physiological and environmental evaluations were conducted on 21 consecutive days. Respiratory rate (RR), rectal temperature (RT) and heart rate (HR) were recorded at 06:00 am and 05:00 pm, while air temperature and relative humidity were recorded from 06:00 am to 05:00 pm. Temperature and Humidity Index (THI) in the SF and ILC indicated severe stress for sheep regardless of the period of the day, and although THI in integrated crop-livestock system was 1% lower than in the sheepfold, there was no statistical differences between the treatments. Ewes from integrated crop-livestock system had lower RR and HR than sheepfold ewes at 06:00 am and 05:00 pm. The afternoon period led the animals to more dangerous situation of thermal stress condition in both treatments, however we suggest that the presence of trees in the ICL system promoted an amelioration of heat stress on grazing ewes.
Keywords: Adaptability; Ewes; Heat stress; Livestock rearing system